Proceedings of the 3rd International Conference on Computer Graphics, Virtual Reality, Visualisation and Interaction in Africa 2004
DOI: 10.1145/1029949.1029960
|View full text |Cite
|
Sign up to set email alerts
|

Impact of large displays on virtual reality task performance

Abstract: A better understanding of how users perform virtual reality tasks may help to build better virtual reality interfaces. In this study, we concentrate on the impact of large displays in virtual reality depending on the tasks and users' characteristics. The two virtual reality tasks studied are the objects manipulation and the navigation in an environment. The users' characteristics studied are the visual attention abilities. Forty subjects participated in the experimentation composed of cognitive tests used to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…However, more research is required to elucidate the precise effect of very large format displays, such as the fulldome, on visual search speed. As noted previously, Tyndiuk et al (2004) found that a larger screen was an advantage in other tasks for users with slower visual search speeds, so performance trade-offs may be more relevant for some tasks than others.…”
Section: Unique Features Of the Fulldomesupporting
confidence: 59%
See 1 more Smart Citation
“…However, more research is required to elucidate the precise effect of very large format displays, such as the fulldome, on visual search speed. As noted previously, Tyndiuk et al (2004) found that a larger screen was an advantage in other tasks for users with slower visual search speeds, so performance trade-offs may be more relevant for some tasks than others.…”
Section: Unique Features Of the Fulldomesupporting
confidence: 59%
“…Interestingly, Tan et al (2006) found that a large display did not produce an advantage in spatial tasks in which an exocentric strategy is optimal, thus highlighting the importance of considering the appropriateness of the task when examining possible advantages for IVEs. Tyndiuk et al (2004) suggest that a large screen advantage may be mediated by the factors of task demands and users' visual attention, because participants with slower visual search ability benefited from a larger screen in manipulation and travel tasks, whereas no difference was shown for faster participants. Similarly, Allen (2000) proposes that the general utility of computer systems varies greatly based on users' spatial and perceptual abilities.…”
Section: Display Sizementioning
confidence: 96%
“…2 that can only be obtained traditionally when using multiple conventional flat displays or a singular large display. Large displays have been shown to act as a benefit with regard to tasks such as those involving visual scanning and both 3D and two-dimensional (2D) data [7][8][9]. In addition to this, it is possible that the visceral illusion of being within a simulated environment, also known as presence, may in itself contribute as a psychological benefit to improved performance on visual tasks [10].…”
Section: Applying Vr To Radiologymentioning
confidence: 99%
“…For interactive digital tasks, the degree of immersion is determined by variables related to sensory experience, such as increasing screen size, sound quality, graphical fidelity or adding 3D display capabilities. There is some evidence that sensory immersion (Ermi and Mayra, 2005) is driven by audiovisual properties of gaming hardware; for example, increased screen size has been associated with greater immersion across a number of studies using desktop displays (Hou et al, 2012;Wu et al, 2011;van den Hoogen et al, 2009), touchscreen systems (Thompson et al, 2012) and head-mounted displays (Tyndiuk et al, 2004;Bowman & McMahan, 2007;Schnall, Hedge & Weaver, 2012). Alternatively, the degree of immersion may be determined by the intrinsic capacity of a task to motivate and engage the cognitive capabilities of the individual.…”
Section: Introductionmentioning
confidence: 99%